2022
DOI: 10.5755/j02.mech.29468
|View full text |Cite
|
Sign up to set email alerts
|

Deform 3D Simulation and Experimental Investigation of Fixtures with Support Heads

Abstract: Thin-walled aluminium parts are employed in a variety of industries, including construction and aerospace. If they are treated to a greater quantity of milling, they are more resistant to deformation. As a result, the stability of the work parts degrades, and the surface roughness increases as a result of this factor. This work proposes the use of a well-designed fixture with support heads to lessen the deformation produced by square thin-walled aluminium plate milling. The suggested fixture system's support h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Jing et al [20] investigated the effects of micro-endmilling cutting parameters on machined surface roughness to determine the best operating conditions. Muthu Mekala et al [21] designed and developed a new fixture to minimize the surface roughness in the end milling of Al6061 workpiece. They concluded that the proposed fixture with the support heads greatly reduces the deformation in the work piece, which significantly impacted the surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…Jing et al [20] investigated the effects of micro-endmilling cutting parameters on machined surface roughness to determine the best operating conditions. Muthu Mekala et al [21] designed and developed a new fixture to minimize the surface roughness in the end milling of Al6061 workpiece. They concluded that the proposed fixture with the support heads greatly reduces the deformation in the work piece, which significantly impacted the surface quality.…”
Section: Introductionmentioning
confidence: 99%